Plasma and salivary irisin response to moderate load/high volume resistance exercise in young, resistance-trained men - Luigi Marano; Sara Missaglia; Eleonora Martegani; Andrea Bonanomi; Chiara Tremolada; Daniela Tavian; Ferdinando Cereda (European Journal of Translational Myology, 2025)
Irisin's response to Resistance Exercise (RE) remains unclear. We investigated plasma and salivary irisin levels following acute moderate load/high volume (ML/HV) RE and explored correlations with muscle damage markers. Eight healthy, resistance-trained young males (23.9 ± 3 yrs) completed one ML/HV RE session (full-body, 30 sets to failure, 70% 1RM). Plasma/saliva irisin, plasma Creatine Kinase (CK), and Visual Analogue Scale (VAS) for muscle soreness were assessed at baseline, 15 min, 24h, and 48h post-exercise. Plasma irisin increased significantly by ~9% (p=0.01) and salivary irisin by ~4% (p=0.02) at 15 min post-exercise, returning towards baseline by 24h. A strong correlation (rho=0.8, p=0.03) existed between percentage changes in plasma and salivary irisin at 15 min. CK and VAS peaked at 24h (p<0.001; p=0.02 vs 48h, respectively), but showed no significant correlation with irisin changes. Acute ML/HV RE elicits a transient increase in plasma and salivary irisin. Saliva may be a useful non-invasive proxy for irisin changes post-RE. This acute irisin response appears independent of EIMD markers in this population. Findings require confirmation in larger studies.